Association of Fibroblast Growth Factor 23 and Calcium in Chronic Kidney Disease Patients - Ghaith Hamza Kamil; Mohammed Mezher Hussein; Raya Ezzat Maroof (Journal of Techniques, 2022)
Chronic kidney disease (CKD) is a growing international health concern with elevating mortality rate in the world today and it is generally a progressive and irreversible issue. It is defined by changes in kidney shape, function, or both lasting at least three months. Renal disease is commonly associated with Abnormalities of minerals and electrolyte. Levels of Ca change and the FGF23 increase early in CKD. This study was designed to show the Correlation between FGF23 and Ca in chronic kidney disease patients. One hundred blood samples (57males and 43 females) from CKD patients have been gathered from Al-Yarmouk Teaching Hospital, Baghdad Teaching Hospital and Al-Karama Teaching Hospital during the period from December 2021 to March 2022 besides 50 samples as apparently healthy control. The age range in the current study was at 33-75 years for CKD patient and 30-65 years for control. The fibroblast growth factor 23 was screened by an ELISA method and serum Calcium, by cobas c111 analyze. Ca, FGF23 is statistically highly significant at p-value =0.001.  The receiver operation characteristic (ROC) curve results revealed that the sensitivity and specificity for FGF23 was 100%. The conclusion of the current study shows that the. FGF 23 was high in all CKD patients and Ca was high in two patients, normal in thirty-seven patients, and decreased in sixty-one patients.